SYNTHESIS AND CHARACTERIZATION OF MAGNETIC-HYDROXY APATITE COMPOSITE USINGONE SPOT COPRECIPITATION METHOD - Mujamilah Mujamilah; Ahmad Furqon Syidik; Grace Tj. Sulungbudi; Wildan z Lubis; Aloma Karo Karo (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2017)
SYNTHESIS AND CHARACTERIZATION OF MAGNETIC-HYDROXY APATITE COMPOSITE USINGONE SPOT COPRECIPITATION METHOD. Nanocomposite of magnetic-hydroxyapatite (MHAP) has the potential to be developed as a biocompatible-biodegradable material for bone cancer diagnosis and therapy. In this study, such composite materials have been successfully synthesized by one-spot coprecipitation method and ultrasonic dispersion. The mass ratio between magnetic and hydroxyapatite fraction were varied to 30:70 (K30), 40:60 (K40) and 50:50 (K50). X-Ray Diffractometer, Transmission Electron Microscope, Fourier Transform-Infrared Spectrometer and Vibrating Sample Magnetometer were used for characterizing the properties of MHAP composite. X-Ray Diffraction pattern reveals the presence of magnetic and HAP phases, confirm the establishment of MHAP composite system. TEM image and FT-IR spectra shows the spherical morphology of magnetic nanoparticles with a size of 10 nm entrapped within HAP nanorod structure without any chemical bonding between the two phase.With such physical composite mechanismand higher energy induce by ultrasonic dispersion process, magnetic fraction of even 50% mass fraction could still be loaded into HAP matrix and provide maximum magnetisation value of 34.6 emu/g. This magnetization value is higher than the result of another study of MHAP synthesis, giving better prospect for bone cancer diagnosis and therapy.